Level or Growth, Which is More Important? Influence of Human Capital on Spillovers from Foreign Direct Investment - Iqbal, Muntasir Mamun; Mumit, Abdul (International Journal of Economics and Financial Issues, 2017)
The paper examines the spillover benefits of foreign direct investment (FDI) in relation to their contribution to economic growth, by utilizing a crossâ€country panel framework over the last four decades. The findings suggest that only when the host country has a certain threshold level of human capital, FDI contributes positively to economic growth through technology diffusion. It is also found that in general terms, the growth of human capital, and not the level of human capital, in the host economy interacts more strongly with FDI to produce positive externalities. This indicates that countries can compensate for their lower levels of human capital stock by substituting it with higher rates of human capital growth. Keywords: Human Capital, Technology Spillover, FDI JEL Classifications: F14, F43